Graduate work-readiness challenges in the Asia-Pacific region and the role of HRM. Issue 2 (14th March 2018) - Verma, Prikshat; Nankervis, Alan; Priyono, Soegeng; Mohd Salleh, Noorziah; Connell, Julia; Burgess, John
Abstract : Purpose: The purpose of this paper is to focus on graduate work-readiness challenges in three Asia Pacific economies (Malaysia, Indonesia and Australia), and the roles of three main stakeholders (government, employers and industry) in the process. The intention of the paper is to design a stakeholder-oriented HRM model to address the identified graduate work-readiness challenges. Design/methodology/approach: A qualitative triangulation method comprising interviews and focus groups was used with participant samples for each country – Australia (19), Indonesia (19) and Malaysia (15). Stakeholder-oriented HRM theory underpins the conceptual framework for the paper. Findings: All three countries are currently experiencing difficulties attracting graduates with the required portfolio of qualifications, skills and personal capabilities. The reported effects include: constraints on national economic growth, future production structures, and long-term socio-economic development. Based on a review of the work-readiness and stakeholder-oriented HRM theory literature, it is posited that graduate work-readiness challenges can be effectively addressed by HR professionals in partnership with other key stakeholders. Research limitations/implications: The study sought the input of only three stakeholder groups for ascertaining graduate work readiness challenges, there is a strong case to include other groups including students/parents and secondary schools. Social implications: Bridging the graduate skills gap between government, employers and educational institutions is an important area in which HR professionals can contribute by reducing the mismatch between demand and supply through influencing and balancing the interests and goals of key stakeholders. Originality/value: This study makes a contribution to the extant literature as it explores the role of HR professionals in relation to a multiple stakeholder strategy to address these challenges in the less-explored Asia Pacific region.